Clastogenic effect of Picrorhiza kurroa rhizome extract on cultured human peripheral blood lymphocytes - Acharya Balkrishna; Hemanth Kumar Manikyam; Vinay K Sharma; Niti Sharma (Shahrekord University of Medical Sciences, 2016)
Introduction: The Picrorhiza kurroa rhizome has a long history of use in Indian Ayurvedic and Chinese system of medicine for the treatment of a wide spectrum of diseases. Today it is viewed as an important therapeutic target in both Western and Eastern medicinal systems. This work was aimed to study the clastogenic effect of Picrorhiza kurroa rhizome extract on cultured human peripheral blood lymphocytes. Methods: Hydroalcoholic extract of rhizome was prepared and mammalian chromosomal aberration test was conducted using cultured human peripheral blood lymphocytes. The study was performed in two independent phases where the human peripheral blood lymphocytes were exposed to various of the extract in absence and presence of metabolic activation system for a continuous and short duration. Results: Picrorhiza kurroa rhizome extract did not induce chromosome aberration up to 2500 μg/mL in final culture concentration in the presence (1% v/v) and absence of metabolic activation. Conclusion: Picrorhiza kurroa rhizome extract is completely safe to be used as a medicine since it manifest its healing effects without causing genotoxicity.